Labor's outcasts : migrant farmworkers and unions in North America, 1934-1966 - Hazelton, Andrew J., 1983- (Working class in American history., 2022)
"In the mid-twentieth century, corporations consolidated control over agriculture on the backs of Mexican migrant laborers through a guestworker system called the Bracero Program. The National Agricultural Workers Union (NAWU) attempted to organize these workers but met with utter indifference from the AFL-CIO. Andrew J. Hazelton examines the NAWU's opposition to the Bracero Program against the backdrop of Mexican migration and the transformation of North American agriculture. His analysis details growers' abuse of the program to undercut organizing efforts, the NAWU's subsequent mobilization of reformers concerned by those abuses, and grower opposition to any restrictions on worker control. Though the union's organizing efforts failed, it nonetheless created effective strategies for pressuring growers and defending workers' rights. These strategies contributed to the abandonment of the Bracero Program in 1964 and set the stage for victories by the United Farm Workers and other movements in the years to come"--